2002
DOI: 10.1038/sj.onc.1205394
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating mutations of the caspase-10 gene in gastric cancer

Abstract: We have analysed the genetic alteration of the entire coding region and all splice sites of caspase-8 and -10 genes in 99 gastric cancers by polymerase chain reaction (PCR)-single strand conformation polymorphism (SSCP) and sequencing. We found LOH of the caspase-8 and -10 in nine (28%) of 32 and in four (15%) of 26 informative cases, respectively. Overall, three of 99 gastric cancers (3%) were found to have the caspase-10 mutations, which were identi®ed in the coding regions of the death eector domain (codon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 26 publications
2
48
1
Order By: Relevance
“…The possibility of SMAD4 involvement in genetic predisposition to diffuse gastric cancer was raised by the observation of foci of adenocarcinoma with signet-ring cells in the stomach of heterozygous knock-out SMAD4 mice [15]. Caspase-10 is another candidate gene for familial gastric cancer, possibly through loss of apoptotic function, as suggested by reports of loss of heterozygosity (LOH) and mutations in coding regions of this gene in 15% and 3%, respectively, of sporadic gastric cancer cases [16]. From all of the probands screened in this study, we identified sequence variants in SMAD4 and Caspase-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of SMAD4 involvement in genetic predisposition to diffuse gastric cancer was raised by the observation of foci of adenocarcinoma with signet-ring cells in the stomach of heterozygous knock-out SMAD4 mice [15]. Caspase-10 is another candidate gene for familial gastric cancer, possibly through loss of apoptotic function, as suggested by reports of loss of heterozygosity (LOH) and mutations in coding regions of this gene in 15% and 3%, respectively, of sporadic gastric cancer cases [16]. From all of the probands screened in this study, we identified sequence variants in SMAD4 and Caspase-10.…”
Section: Discussionmentioning
confidence: 99%
“…CA, USA) following the manufacturer's instructions. Caspase-10 genomic sequences were amplified using primer sequences and conditions previously described in [16]. Genomic DNA (25-100 ng) was amplified by PCR using the following cycling conditions: 30 s at 94°C, 30 s at the appropriate annealing temperature, and 45 s at 72°C for 35 cycles.…”
Section: Polymerase Chain Reaction-single-strand Conformation Polymormentioning
confidence: 99%
“…92 Recently, caspase-10, along with caspase-8, was shown to be essential for mediating NF-kB-dependent inflammatory responses in antiviral signalling. 93 Missense and inactivating mutations in casp10 gene have been reported to be associated with some cases of the autoimmune lymphoproliferative syndrome II (ALPS II), 94 non-Hodgkin lymphoma 95 and gastric cancer, 96 however it is unclear whether these mutations directly contribute to the disease phenotype.…”
Section: The Apoptotic Caspases S Kumarmentioning
confidence: 99%
“…Acquired inactivating mutations of caspase-10 have been identified in tumor cells from patients with nonHodgkin's lymphomas (Shin et al, 2002a) and solid tumors (Harada et al, 2002;Park et al, 2002;Shin et al, 2002b). Chemotherapeutic agents such as etoposide and doxorubicin induce casp-10 gene transcription in a p53-dependent manner (Rikhof et al, 2003) and arsenic trioxide stimulates casp-10 gene transcription by promoting histone H3 phosphoacetylation in acute promyelocytic leukemia cells (Li et al, 2002).…”
Section: Introductionmentioning
confidence: 99%